Multilevel mesh workflows towards CONUS scale watersheds: How small should triangles be to capture stream curvature for hydrological modeling?. (December 2019) - Leonard, Lorne
Abstract: Generating quality meshes for hydrological modeling is challenging. This article demonstrates using mesh workflows to incorporate national stream networks into very large dynamic meshes for distributed High Performance Computing (HPC). A multilevel quadtree is used to partition watersheds and merge stream networks ranging from hill-slope to four level-4 Hydrological Unit Code (HUC) scales, generating mesh sizes from hundreds to tens of millions of triangles. By using a mesh workflow, it is demonstrated how users control mesh quality, including triangle sizes, and the removal of small triangles and slivers. Four watersheds are studied, ranging in scale from Shale Hills (hill-slope) to the Chesapeake Bay (177, 968 sq. km.) and are used to compare mesh characteristics with user parameters and different elevation sources to generate a spectrum of multilevel quadtree meshes. By using triangles to represent land surface and stream networks, stream curvature is lost and the mesh workflow is used to demonstrate what parameters are important to maintain stream characteristics. To meet HPC constraints, the multilevel quadtree is demonstrated by picking quadtree tiles along a storm path to show how users can combine quadtree tiles at multiple levels to concentrate HPC resources for hydrological science research. Graphical abstract: Image 1 Highlights: Quality mesh quadtree tiles at hill-slope to CONUS scale models for distributed HPC. Merging national stream networks with large quadtree TIN meshes. User parameters to predict and evaluate mesh qualities. Mesh workflow to remove slivers and thin and small triangles. Examining where stream curvature is lost with different mesh resolutions and characteristics.